Current Concepts in Fluid Therapy in Horses - Crabtree, Naomi E.; Epstein, Kira L. (Frontiers in Veterinary Science, 2021)
Despite the frequent inclusion of fluid therapy in the treatment of many conditions in horses, there are limited studies available to provide evidenced-based, species-specific recommendations. Thus, equine fluid therapy is based on the application of physiology and extrapolation from evidence in other veterinary species and human medicine. The physiologic principles that underly the use of fluids in medicine are, at first glance, straightforward and simple to understand. However, in the past 20 years, multiple studies in human medicine have shown that creating recommendations based on theory in combination with experimental and/or small clinical studies does not consistently result in best practice. As a result, there are ongoing controversies in human medicine over fluid types, volumes, and routes of administration. For example, the use of 0.9% NaCl as the replacement fluid of choice is being questioned, and the theoretical benefits of colloids have not translated to clinical cases and negative effects are greater than predicted. In this review, the current body of equine research in fluid therapy will be reviewed, connections to the controversies in human medicine and other veterinary species will be explored and, where appropriate, recommendations for treatment will be made based on the available evidence.